Bond durability and service life prediction of BFRP bars to steel FRC under aggressive environmental conditions - Alaa Taha (17302783) (2021)
This study presents an experimental investigation on the bond durability of helically wrapped basalt fiber reinforced polymer (BFRP) bars embedded in plain and steel fiber reinforced concrete (SFRC) under the combined effect of simulated oceanic environment and elevated temperatures. A total of sixty-three pullout specimens were tested to study the effect of concrete type (plain and SFRC), immersion temperature (35 °C and 60 °C), immersion duration (30, 60, and 90 days), and fiber volume fraction (Vf) of steel fibers (0.5% and 1%). The bond durability of the used bars was examined based on the bond strength and mode of failure. The BFRP bars at the interface along the embedment length with concrete were analyzed using scanning electron microscopy. In addition, the BPE and CMR models for bond-slip behavior were calibrated considering the immersion temperature, concrete type, and exposure duration. The experimental results revealed that the pullout specimens with Vf = 1% showed higher bond durability performance than specimens with Vf = 0.5%, particularly at high temperatures. Furthermore, the CMR model showed better correlation with the experimental data than the BPE model. Moreover, the 50 years service life prediction showed bond strength retentions of BFRP bars that ranged from 54% to 86% depending on the type of concrete (plain and SFRC), surrounding mean annual temperature (5 °C to 35 °C), and degree of moisture (dry, moist, and moisture saturated). Other Information Published in: Composite Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compstruct.2021.114034